Inhibition of sphingosine 1-phosphate protects mice against chondrocyte catabolism and osteoarthritis. Issue 9 (September 2021) - Cherifi, C.; Latourte, A.; Vettorazzi, S.; Tuckermann, J.; Provot, S.; Ea, H.-K.; Ledoux, A.; Casas, J.; Cuvillier, O.; Richette, P.; Ostertag, A.; Hay, E.; et al.
Summary: Objective: Cartilage loss observed in osteoarthritis (OA) is prevented when osteoclasts in the subchondral bone are inhibited in mice. Here, we investigated the role of the osteoclast secretome and of the lipid mediator sphingosine 1-phosphate (S1P) in chondrocyte metabolism and OA. Materials and methods: We used SphK1 LysMCre and wild type mice to assess the effect of murine osteoclast secretome in chondrocyte metabolism. Gene and protein expressions of matrix metalloproteinase ( Mmp ) were quantified in chondrocytes and explants by RT-qPCR and Western blots. SphK1 LysMCre mice or wild type mice treated with S1P2 receptor inhibitor JTE013 or anti-S1P neutralizing antibody sphingomab are analyzed by OA score and immunohistochemistry. Results: The osteoclast secretome increased the expression of Mmp3 and Mmp13 in murine chondrocytes and cartilage explants and activated the JNK signaling pathway, which led to matrix degradation. JTE013 reversed the osteoclast-mediated chondrocyte catabolism and protected mice against OA, suggesting that osteoclastic S1P contributes to cartilage damage in OA via S1P/S1P2 signaling. The activity of sphingosine kinase 1 (SphK1) increased with osteoclast differentiation, and its expression was enhanced in subchondral bone of mice with OA. The expression of Mmp3 and Mmp13 in chondrocytes was low upon stimulation with the secretome of Sphk1 -lacking osteoclasts. Cartilage damage was significantly reduced in SphK1 LysMCre mice, but not the synovial inflammation. Finally, intra-articular administration of sphingomab inhibited the cartilage damage and synovial inflammation. Conclusions: Lack of S1P in myeloid cells and local S1P neutralization alleviates from osteoarthritis in mice. These data identify S1P as a therapeutic target in OA.